2019
DOI: 10.1111/hepr.13333
|View full text |Cite
|
Sign up to set email alerts
|

Albumin–bilirubin score indicates liver fibrosis staging and prognosis in patients with chronic hepatitis C

Abstract: Aim Albumin–bilirubin (ALBI) grade was investigated to predict prognosis of patients with cirrhosis. It was defined using the ALBI score calculated based on serum total bilirubin and albumin, which represent liver function. The diagnostic accuracy for liver fibrosis staging in patients with chronic hepatitis using the ALBI score has not been investigated well. This study aimed to evaluate the diagnostic abilities of the ALBI score for liver fibrosis staging in chronic hepatitis and cirrhosis in Japanese patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 42 publications
6
31
2
1
Order By: Relevance
“…Currently, application of ALBI score is limited in cirrhosis patients, similar to the Child Pugh score. However, our previous studies have clari ed that the ALBI score has the potential to differentially diagnose brosis stage 4 from stage 1 to 3 in HCV infection, HBV infection, and PBC [34][35][36]. In AIH, ALBI score was able to diagnose brosis stage 4 regardless of the in ammatory severity of the hepatitis at any stage of the disease.…”
Section: Discussionmentioning
confidence: 94%
“…Currently, application of ALBI score is limited in cirrhosis patients, similar to the Child Pugh score. However, our previous studies have clari ed that the ALBI score has the potential to differentially diagnose brosis stage 4 from stage 1 to 3 in HCV infection, HBV infection, and PBC [34][35][36]. In AIH, ALBI score was able to diagnose brosis stage 4 regardless of the in ammatory severity of the hepatitis at any stage of the disease.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that ALBI combined with the TNM classification predicts recurrence-free survival of patients after hepatectomy [33]. Furthermore, lower ALBI correlates with longer HCC-free survival of patients with chronic HCV hepatitis [34].…”
Section: Discussionmentioning
confidence: 97%
“…The ALBI score was originally proposed as an indicator for hepatic functional reserve in patients with HCC. 16 However, the ALBI score was recently reported to indicate liver fibrosis and prognosis in patients with chronic hepatitis C. 26 We calculated it for evaluating hepatic functional reserve. It has been reported that improvement of the synthetic ability of the liver and increased albumin were observed in HCV-infected patients who obtained an SVR with DCV + ASV.…”
Section: Discussionmentioning
confidence: 99%
“…The ALBI score was originally proposed as an indicator for hepatic functional reserve in patients with HCC . However, the ALBI score was recently reported to indicate liver fibrosis and prognosis in patients with chronic hepatitis C . We calculated it for evaluating hepatic functional reserve.…”
Section: Discussionmentioning
confidence: 99%